Agents and Data Mining Interaction 6th International Workshop on Agents and Data Mining Interaction, ADMI 2010, Toronto, ON, Canada, May 11, 2010, Revised Selected Papers - Cao, Longbing; Bazzan, Ana L. C.; Gorodetsky, Vladimir; Mitkas, Pericles A.; Weiss, Gerhard; Yu, Philip S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 6th International Workshop on Agents and Data Mining Interaction, ADMI 2010, held in Toronto, Canada, in May 2010. The 15 revised full papers presented were carefully reviewed and selected from 37 submissions. The papers are organized in topical sections on agents for data mining; data mining for agents; data mining in agents; and agent mining applications.
Agents for Data Mining -- Finding Useful Items and Links in Social and Agent Networks -- Integrating Workflow into Agent-Based Distributed Data Mining Systems -- Pilot Study: Agent-Based Exploration of Complex Data in a Hospital Environment -- Multi-agent Information Retrieval in Heterogeneous Industrial Automation Environments -- Data Mining for Agents -- A Data Mining Approach to Identify Obligation Norms in Agent Societies -- Probabilistic Modeling of Mobile Agents$1 (BTrajectories -- Real-Time Sensory Pattern Mining for Autonomous Agents -- Data Mining in Agents -- Analyzing Agent-Based Simulations of Inter-organizational Networks -- Clustering in a Multi-Agent Data Mining Environment -- Time-Based Reward Shaping in Real-Time Strategy Games -- Wise Search Engine Based on LSI -- Pattern Recognition in Online Environment by Data Mining Approach -- Agent Mining Applications -- A Multiple System Performance Monitoring Model for Web Services -- Implementing an Open Reference Architecture Based on Web Service Mining for the Integration of Distributed Applications and Multi-Agent Systems -- Minority Game Data Mining for Stock Market Predictions.s
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Database Management; Computer Communication Networks; Data Mining and Knowledge Discovery